Indentation of a pressurized silicon stomach model – A non-invasive study of gastric wall stiffness and pressurized gastric content stiffness. (November 2022) - Liao, Donghua; Mark, Esben Bolvig; Nedergaard, Rasmus Bach; Jensen, Lars Rosgaard; Bertoli, Davide; Frøkjær, Jens Brøndum; Yu, Donghong; Zhao, Jingbo; Brock, Christina; Drewes, Asbjørn Mohr
Abstract: Background and aims: Evaluation of gastric wall stiffness and intragastric pressure is essential for detailed assessments of gastric accommodation. However, non-invasive assessments are needed for large scale clinical studies and none of the existing methods takes abdominal wall effect into the calculation. This study aimed to assess gastric wall stiffness and gastric content stiffness as a proxy for intragastric pressure using novel mechanical modeling and non-invasive indentation tests on a silicon stomach model. Methods: A silicon stomach model (scaling 1:1 with the human stomach) was indented using a pressure algometer at intragastric pressures from 0 to 0.8 kPa. Wall thicknesses and luminal cross-sectional areas along the stomach were measured with ultrasound images. The gastric wall stiffness was compared between measurements from tensile tests on strips cut from the silicon stomach and estimations from a shell indentation model. The pressurized gastric content stiffness was predicted from a bonded two-layer axisymmetric half-space indentation model. Results: The gastric wall stiffness estimated from the shell indentation model showed no difference to measurements from the mechanical tests on the cutting strips (p = 0.14). The predicted gastric content stiffness was strongly associated with the intragastric pressure (r > 0.83, p < 0.001). Conclusions: The mechanical model developed in this study can simultaneously predict the gastric wall stiffness and the pressurized gastric content stiffness. In future studies, the method can be applied to reveal intragastric pressure conditions non-invasively via the pressurized gastric content stiffness during gastric accommodation and emptying such as with magnetic resonance imaging. Graphical abstract: Image 1 Highlights: Gastric accommodation evaluation requires gastric volume and pressure recordings. Intragastrical pressure can only be measured invasively. The gastric content stiffness can be used as a proxy of the intragastric pressure. We assessed gastric content stiffness using non-invasive indentation test. Gastric content stiffness has potential in clinical accommodation evaluations.